2007
DOI: 10.1179/174329407x169458
|View full text |Cite
|
Sign up to set email alerts
|

TiC reinforced composite layer formation on Al–Si alloy by laser processing

Abstract: Al-Si alloy was laser surface treated with various compositions of TiC and Ni under different laser processing parameters to produce a TiC reinforced composite layer on it. The study shows that TiC composite layer is formed when the composition is 75TiC-25Ni (wt-%) and laser power 2 . 5 kW and scan speed 0 . 2 m min 21 . The layer exhibited an average microhardness of y750 HV, which is free from pores as well as cracks and contained TiC and Al-Si phases distributed in the Ni-Al matrix. Mechanical strength of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In the previous study 4 TiC was reinforced with Ni-Al intermettalic on Al-Si alloy. The study showed that, though the TiC was well bounded with Ni-Al intermetalics, the clad layer exhibited inconsistence of hardness distribution due to soft nature of Ni-Al intermetallics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous study 4 TiC was reinforced with Ni-Al intermettalic on Al-Si alloy. The study showed that, though the TiC was well bounded with Ni-Al intermetalics, the clad layer exhibited inconsistence of hardness distribution due to soft nature of Ni-Al intermetallics.…”
Section: Introductionmentioning
confidence: 99%
“…Laser surface engineering provides several unique surface properties as compared to the conventional methods. Processability of the materials using laser involves rapid heating and subsequent cooling, these results in non-equilibrium phase formation and also a strong bond between the layer and substrate 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser melt injection of WC particles on aluminium surface was studied by Li et al 14 They demonstrated that the powder should be fed from the back side of the laser beam to achieve appropriate surface enhancement effect and the depth of the melt layer increased first and, then, decreased with increasing laser power. Laser processing of TiC reinforced composite layer on Al–Si alloy surface was investigated by Viswanathan et al 15 The findings revealed that the layer was free from pores and TiC and Al–Si phases were almost uniformly distributed in the Ni–Al matrix. Laser ablation of archaeological bronze plate surface underwater was investigated by Dajnowski.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the important groups of surface engineering tools because of their characteristic features, such as rapid heating and melting, which facilitate the possibility of extended solid solution, fine microstructure, composition homogenisation, excellent metallurgical interface, etc. [3][4][5][6] Additionally, the other advantages of LSM over conventional processes are short processing time, flexibility in operation, economy in time, energy, material consumption. etc.…”
Section: Introductionmentioning
confidence: 99%